Diagnostic and Prognostic Implications of FGFR3high/Ki67high Papillary Bladder Cancers - Geelvink, Mirja; Babmorad, Armin; Maurer, Angela; Stöhr, Robert; Grimm, Tobias; Bach, Christian; Knuechel, Ruth; Rose, Michael; Gaisa, Nadine T. (International Journal of Molecular Sciences, 2018)
Prognostic/therapeutic stratification of papillary urothelial cancers is solely based upon histology, despite activated FGFR3-signaling was found to be associated with low grade tumors and favorable outcome. However, there are FGFR3-overexpressing tumors showing high proliferation-a paradox of coexisting favorable and adverse features. Therefore, our study aimed to decipher the relevance of FGFR3-overexpression/proliferation for histopathological grading and risk stratification. N = 142 (n = 82 pTa, n = 42 pT1, n = 18 pT2-4) morphologically G1⁻G3 tumors were analyzed for immunohistochemical expression of FGFR3 and Ki67. Mutation analysis of FGFR3 and TP53 and FISH for FGFR3 amplification and rearrangement was performed. SPSS 23.0 was used for statistical analysis. Overall FGFR3high/Ki67high status (n = 58) resulted in a reduced ∆mean progression-free survival (PFS) (p < 0.01) of 63.92 months, and shorter progression-free survival (p < 0.01; mean PFS: 55.89 months) in pTa tumors (n = 50). FGFR3mut/TP53mut double mutations led to a reduced ∆mean PFS (p < 0.01) of 80.30 months in all tumors, and FGFR3mut/TP53mut pTa tumors presented a dramatically reduced PFS (p < 0.001; mean PFS: 5.00 months). Our results identified FGFR3high/Ki67high papillary pTa tumors as a subgroup with poor prognosis and encourage histological grading as high grade tumors. Tumor grading should possibly be augmented by immunohistochemical stainings and suitable clinical surveillance by endoscopy should be performed.
EVALuna2:205512